STUDI INTERAKSI LIGAN PEPTIDOID DAN PEPTIDA DENGAN ENZIM PROTEASE NS3/NS2B VIRUS DENGUE - Amelia, Fitri (IAIN Batusangkar, 2014)
Peptide has a high bioactivity and specificity, possess low interaction to other drugs and has a low toxicity values . However, peptide -based drugs have drawbacks, which are rapidly degraded in the digestive system due to the activity of the protease enzyme that peptide drugs are not suitable to be developed as an oral medication. The purpose of this study to determine whether the value of peptidoid is higher than the peptide and to analize the influences between interaction and DG of Peptidoid KGPE is the higher than its peptide, -16.13874 kkal/mol. The high number of hydrogen donor for Hydogen bonding derived ligand can lower the value of KiKey words: peptidoid,peptide-base drug, protease NS3/NS2B